تحليل و قياس المخاطر المصرفية بليبيا (دراسة مقارنة بين مصرف الصحارى و مصرف التجاري ) - الساعدي أسامة جمعة (Surman Journal of Science and Technology, 2022)
Abstract: This study aimed to investigate the risks encountered by (Sahara and Tejare) bank. And to compare those risks over ten years period from (2000 till 2010). Known that those two banks are the main commercial banks in Libya. The risks in both banks have been identified together with their types for each bank and their effects on revenue fluctuations. The findings showed differences in the statistical analysis between the different types of risks experienced by each bank and the degree of risk in each bank ranging from ( Loan , interest rate , liquidity and capital). There is also evidence of variance between the two banks in the nature of nature and when comparing each ban k alone . Fluctuation degree of Bank profitability (Z) - Credit Loss Rate ( LP ) - Sensitivity Percentage (ST) Fluctuation of interest rates current in the market (F C) - Liquidity Percentage (LIQ) Percentage of deposits loaded with interests to total deposits (TD ) Equity rate to total assets (E) Equity rate to Risk assets (E)